Different Interactive Effects of Metformin and Acarbose With Dietary Macronutrient Intakes on Patients With Type 2 Diabetes Mellitus: Novel Findings From the MARCH Randomized Trial in China - An, Yu; Li, Yinhui; Bian, Nannan; Ding, Xiaoyu; Chang, Xiaona; Liu, Jia; Wang, Guang (Frontiers in Nutrition, 2022)
Antidiabetic oral agents and nutrition management are frequently used together as ﬁrst-line therapies for type 2 diabetes mellitus (T2DM). However, little is known about their interaction. The interactive effect of two classic antidiabetic medications of acarbose and metformin with dietary intakes of macronutrients on glycemic control and cardiometabolic risk factors was investigated in the March randomized clinical trial. The patients with newly diagnosed T2DM from China were included in the trial. Participants were randomized to receive either metformin or acarbose monotherapy as the initial treatment, followed by a 24-week treatment phase, during which add-on therapy was used if necessary. Dietary intakes of carbohydrate, protein, fat and total energy were calculated by a 24-h food diary recall method. Linear mixed-effect models combined with subgroup analysis were used to investigate independent and interactive effects of drugs and diet on clinical outcomes. Data analysis was performed on 551 of the 788 patients randomly assigned to treatment groups. Metformin therapy was independently associated with higher triglycerides (TG, β=0.471, P=0.003), 2-h postprandial plasma glucose (2hPPG, β=0.381, P=0.046) but lower low-density lipoprotein cholesterol (LDL-C, β=-0.149, P=0.013) compared with acarbose therapy. Higher carbohydrates and lower fat intakes were independently associated with poorer glycemic control, less weight loss and greater insulin secretion. Higher total energy intake was also independently associated with higher fasting (β=0.0002, P=0.001) and postprandial blood glucose (β=0.0004, P=0.001). Interaction and subgroup analyses demonstrated that glucagon-like peptide-1 (GLP-1) was positively related to total energy (β=0.268, P=0.033), carbohydrates intake and insulin secretion (β=2045.2, P=0.003) only in acarbose group, while systolic blood pressure (SBP) was negatively related to protein intake in metformin group (β=23.21, P=0.014). The results of this study showed that metformin and acarbose mainly exerted different interactive effects with dietary energy, carbohydrate and protein intakes on GLP-1 secretion, insulin release and SBP. The interaction between drug therapy and nutrition intervention in glycemia highlights the complexity of combination therapy.